PERAN KEBIJAKAN HUTANG DALAM MEMODERASI HUBUNGAN INVESTMENT OPPORTUNITY SET DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Putu Cita Ayu; Ni Putu Ayu Kusumawati (Universitas Pendidikan Nasional, 2020)
Company value is the investor's perception of the company's success rate that is often associated with stock prices. Global competition as it is today makes each company increasingly improve performance so that its objectives can be achieved. This research was conducted at the Indonesia Stock Exchange by accessing www.idx.co.id and by conducting a literature study at the Indonesian Capital Market Directory (ICMD) located at the BEI Denpasar branch office. By using purposive sampling technique the number of samples is 66 companies. The results showed that the Investment opportunity set influences company value. Dividend policy affects the value of the company. Debt policy is not able to moderate the effect of investment opportunity set on the value of the company but is able to moderate the effect of dividend policy on the firm value